Synthesis, Transport, and Thermoelectric Studies of Topological Dirac Semimetal Cd3AS2 for Room Temperature Waste Heat Recovery and Energy Conversion - (:unkn) unknown (My University, 2017)
ABSTRACT SYNTHESIS, TRANSPORT, AND THERMOELECTRIC STUDIES OF TOPOLOGICAL DIRAC SEMIMETAL CD3AS2 FOR ROOM TEMPERATURE WASTE HEAT RECOVERY AND ENERGY CONVERSION by The University of Wisconsin-Milwaukee, 2017 Under the Supervision of Professor Nikolai Kouklin Rising rates of the energy consumption and growing concerns over the climate change worldwide have made energy efficiency an urgent problem to address. Nowadays, almost two-thirds of the energy produced by burning fossil fuels to generate electrical power is lost in the form of the heat. On this front, increasing electrical power generation through a waste heat recovery remains one of the highly promising venues of the energy research. Thermo-electric generators (TEGs) directly convert thermal energy into electrical and are the prime candidates for application in low-grade thermal energy/ waste heat recovery. The key commercial TE materials, e.g. PbTe and Bi2Te3, have room temperature ZT of less than 1, whereas ZT exceeding 3 is required for a TEG to be economically viable. With the thermoelectric efficiency typically within a few percent range and a low efficiency-to-cost ratio of TEGs, there has been a resurgence in the search for new class of thermo-electric materials for developing high efficiency thermo-to-electric energy conversion systems, with phonon-glass electron-crystal materials holding the most promise. Herein, we focus on synthesis, characterization and investigation of electrical, thermo-electrical and thermal characteristics of crystalline Cd3As2, a high performance 3D topological Dirac semimetal with Dirac fermions dispersing linearly in k3-space and possessing one of the largest electron mobilities known for crystalline materials, i.e. ~104-105cm2V-1s-1. Suppression of carrier backscattering, ultra-high charge carrier mobility, and inherently low thermal conductivity make this semimetal a key candidate for demonstrating high, device-favorable S and in turn ZT. In this work, a low-temperature vapor-based crystallization pathway was developed and optimized to produce free standing 2D cm-size crystals in Cd3As2. Compared to the bulk crystals produced in previous studies, e.g. Piper-Polich, Bridgman, or flux method, Cd3As2 samples were synthesized over a considerably shorter time ( only a few hours), were single crystals and highly stochiometric. A high thermopower of up to 613 μV K−1 and the electrical conductivity of ~ 105 S/m were registered within the temperature range of 300–400 K. A 1ω-method based on the transfer function was applied to probe a thermal conductivity, k of Cd3As2 platelets. The results yield k of ~2.4 W/m.K in the confirmation that the thermal conductivity of Cd3As2 crystals is to approach the amorphous limit at the room temperature. With its peak thermopower attained at the low temperature range of ~300-400 K, high electrical conductivity and amorphous limit thermal conductivity, crystalline Cd3As2 grown via a low-T vapor based method demonstrates ZT >3; the results confirm that as-produced Cd3As2 platelets hold a high promise and is another phonon-glass electron-crystal TE material for the development of next generation, high efficiency thermo-electric generators and refrigerators operating under normal conditions.
Keywords: Crystalline Cadmium Arsenide Platelet; Dirac Semimetals; Low-T CVD; Thermal Conductivity; Thermoelectric Generators; Topological Materials